Exploring Adolescent Development in Diverse Cultures: Insights and Implications - Maspul, Kurniawan Arif; Bruneton, Catherine; Naing, Thet Ko Ko; Popov, Roman; Saleh, Perihan (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
This study delves at teenage behavior and interactions in many cultural contexts, providing vital insights into their development. This study sheds light on the multifaceted aspects of adolescent behavior, peer relationships, and their quest for independence by employing established theories such as adolescence theory, Erikson’s psychosocial development theory, Bandura’s social cognition theory, Piaget’s cognitive development theory, and Bronfenbrenner’s ecological systems theory. Observations were carried out in Morocco, Egypt, Myanmar, Kyiv, and Jakarta to document the experiences of teenagers aged 12 to 14. The stories emphasize topics such as solidarity, independence, companionship, and identity exploration. The findings include observations such as unity among Moroccan girls, assertive self-expression in Egyptian males, pleasant mixed-gender relationships in Myanmar, and worrying behavior in a Ukrainian adolescent. Adolescent growth is influenced by cultural environment, peer connections, and ecological systems, according to these narratives. The study advances our understanding of teenage experiences across cultures, informing interventions and policies that promote healthy development and well-being.